Perceived Control, Severity, Certainty, and Emotional Fear: Testing an Expanded Model of Deterrence. (July 2020) - Roche, Sean Patrick; Wilson, Theodore; Pickett, Justin T.
Objectives: Growing evidence indicates that criminologists should incorporate emotional states, such as fear, into standard deterrence frameworks. Within the fear of crime literature, there is empirical support for the "sensitivity to risk" model, which posits perceived victimization control and severity drive certainty perceptions, and these cognitions, in turn, drive fear of crime. We apply this logic to offender decision-making. Methods: Using a sample of young adults ( N = 829), an anonymous online survey, and path analysis, this study investigates an expanded model of deterrence. Results: Perceived control over apprehension directly reduced perceptions of the certainty of being apprehended. Perceived severity was both directly and indirectly, through perceived certainty, associated with greater fear of apprehension. Fear of apprehension is negatively associated with reported criminal propensity, and the effects of cognitive judgments of control, severity, and certainty have an indirect effect on reported criminal propensity via fear of apprehension. Conclusions: Our findings illustrate the need to better understand the psychological and emotional aspects of deterrence. Individuals do not simply consult their preformed certainty perceptions when considering crime. Identifying all of the relevant cognitions and the emotions is critical for advancing criminological theories and improving crime policies.